2018
DOI: 10.1200/jco.2018.36.34_suppl.189
|View full text |Cite
|
Sign up to set email alerts
|

Opioid dose reduction and pain control with medical cannabis.

Abstract: 189 Background: The use of medical cannabis (MC) for palliation of symptoms is on the rise in cancer and rheumatological patients. Whether there is a potential for opioid dose reduction (ODR) and or quality of life improvements (QOL) is unclear. Methods: A retrospective cohort was evaluated to understand the pattern of care and QOL outcomes with MC use across rural multidisciplinary practices in New Mexico. MC use (> 1 mo.), EMR interrogation, urine toxicology screening were used to identify patients. QOL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A preliminary cohort study reported a clinically and statistically significant relationship between enrolment in a New Mexico Medical Cannabis Program (MCP) and pain reduction, opioid prescription cessation (no prescription of opioid medication within the last 3 months), reduction in daily intravenous (IV) injection of opioid medications, reduced hospitalization due to prescription opioid medications (POMs) [67], reduced health care costs [67], and improvements of overall quality of life, social life, concentration, and activity levels [68]. A 41% opioid dose reduction (ODR) was also achieved using medical cannabis in cancer and rheumatological patients [69].…”
Section: Cannabinoids As An Alternative To Opioidsmentioning
confidence: 99%
“…A preliminary cohort study reported a clinically and statistically significant relationship between enrolment in a New Mexico Medical Cannabis Program (MCP) and pain reduction, opioid prescription cessation (no prescription of opioid medication within the last 3 months), reduction in daily intravenous (IV) injection of opioid medications, reduced hospitalization due to prescription opioid medications (POMs) [67], reduced health care costs [67], and improvements of overall quality of life, social life, concentration, and activity levels [68]. A 41% opioid dose reduction (ODR) was also achieved using medical cannabis in cancer and rheumatological patients [69].…”
Section: Cannabinoids As An Alternative To Opioidsmentioning
confidence: 99%
“…Similar findings were noted in an observational by Bulbul et al . in 2018,[ 15 ] where the authors reported a 41% reduction in overall opioid consumption with the use of cannabinoids.…”
Section: Mechanism Of Actionmentioning
confidence: 99%